1988
DOI: 10.1021/ic00279a016
|View full text |Cite
|
Sign up to set email alerts
|

Orthometalation of m-bis(dimethylaminomethyl)benzene: crystal structure and chemistry of trans-Rh(III)Cl2[C6H3(CH2NMe2)2-o,o'](H2O)

Abstract: From the reaction of m-(Me2NCH2)2C6H4 with aqueous rhodium trichloride in ethanol the ortho-metalated product trans-Rhn,Cl2(N-C-N)(H20) could be isolated in 45% yield (N-C-N = C6H3(CH2NMe2)2-o,oO. Its solid-state structure was determined by an X-ray diffraction study. Crystals are monoclinic, space group P7\jn, with lattice parameters a = 9.070 (1) Á, b = 17.277 (3) Á, c = 9.855 (1) Á, ß = 91.34 (1)°, V = 1543.9 (4) Á3, Z = 4, and ¿(caled) = 1.648 g cm"3. Refinement with 3710 observed reflections converged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 1 publication
2
19
0
1
Order By: Relevance
“…ligand provides N,C,N'-terdentate coordination. [6] Macrocyclic aryldiamines also display this C ± H bond activation behaviour. [7] In general, other platinum group metal complexes do not undergo selective cyclometallation at C-2 of the 1,3-bis[(dimethylamino)methyl]benzene (NCN) ligand.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…ligand provides N,C,N'-terdentate coordination. [6] Macrocyclic aryldiamines also display this C ± H bond activation behaviour. [7] In general, other platinum group metal complexes do not undergo selective cyclometallation at C-2 of the 1,3-bis[(dimethylamino)methyl]benzene (NCN) ligand.…”
mentioning
confidence: 96%
“…Aryl ligand precursors that contain two meta-positioned S-donor substituents can be cyclometallated selectively at the central C aryl ± H bond by a number of palladium(ii) complexes [Eq. (6)]. Early work by Shaw et al [15] had suggested that only arenes containing bulky groups at the S-donor atoms could be successfully activated at the central C ± H bond.…”
mentioning
confidence: 99%
“…Therefore, initial coordination of the NCN pincer ligand to the metal precursor, which is an essential prerequisite for cyclometalation, is less favored than with the corresponding PCP and SCS pincer ligands. Moreover, this situation results in kinetically rather than thermodynamically controlled reaction pathways, and consequently, ortho , para doubly metalated products rather than ortho , ortho ‐biscyclometalated species are obtained (Scheme ) 20, 21. Insertion of a Me 3 Si substituent as a directing group on the aromatic system (R 3 =Me 3 Si) successfully suppresses undesired ortho , para ‐metalation 22…”
Section: Strategies For the Metalation Of Pincer Ligandsmentioning
confidence: 99%
“…Daher ist die für eine Cyclometallierung notwendige Wechselwirkung des NCN‐Pinzetten‐Liganden mit dem Metall‐Ausgangskomplex schwächer als bei den entsprechenden PCP‐ und SCS‐Liganden. Des Weiteren führt diese Situation zur bevorzugten Bildung des kinetisch kontrollierten doppelt metallierten ortho , para ‐Produkts anstelle des thermodynamisch kontrollierten biscyclometallierten ortho , ortho ‐Produkts (Schema ) 20, 21. Allerdings kann die unerwünschte ortho , para ‐Metallierung durch die Einführung eines Me 3 Si‐Substituenten als dirigierende Gruppe am aromatischen System (R 3 =Me 3 Si) erfolgreich unterdrückt werden 22…”
Section: Strategien Für Die Metallierung Von Pinzetten‐ligandenunclassified